2023
DOI: 10.1186/s10195-023-00683-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcomes and return to play after arthroscopic rotator cuff repair in overhead athletes: a systematic review

Abstract: Background Rotator cuff tear injuries in overhead athletes are common and may lead to chronic pain and joint disability, impairing sport participation and leading to premature retirement. The improvement of the patient reported outcome measures (PROMs) was evaluated, as were the time and level of return to sport and the rate of complication in overhead athletes who had undergone arthroscopic rotator cuff repair. Methods This systematic review was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Most of the athletes return to physical activity after at least 6 months from surgery. 18,26,51,56 Reuter et al 51 and Kholinne et al 26 reported longer time to RTS, 8.3 and 10.3 months, respectively. This discrepancy could be correlated with the heterogeneity of studied populations and sports.…”
Section: Time From Surgerymentioning
confidence: 97%
See 2 more Smart Citations
“…Most of the athletes return to physical activity after at least 6 months from surgery. 18,26,51,56 Reuter et al 51 and Kholinne et al 26 reported longer time to RTS, 8.3 and 10.3 months, respectively. This discrepancy could be correlated with the heterogeneity of studied populations and sports.…”
Section: Time From Surgerymentioning
confidence: 97%
“…Most of the athletes return to physical activity after at least 6 months from surgery 18,26,51,56 . Reuter et al 51 and Kholinne et al 26 reported longer time to RTS, 8.3 and 10.3 months, respectively.…”
Section: Criteria For Return To Sportmentioning
confidence: 98%
See 1 more Smart Citation
“…Meniscal tears have different aetiologies and injury patterns [44, 47, 60]. First, a distinction is made between acute and degenerative tears [39, 56]. Acute tears are commonly the result of trauma or sports injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have also yet to more thoroughly consider matters related to injury recurrence after surgery in this context. For example, long-term observation studies have demonstrated that 19% of meniscus repairs fail [29], and the surgical method applied for such repairs, the all-inside technique, has shown a higher probability of returning to the game after recovery to the level before injury than the inside-out technique; at the same time, the injury recurrence rate is higher [30]. In addition, osteoarthritis can occur secondary to meniscus damage [31], making evaluation through remeasurement of functional aspects a necessity in follow-up studies to identify the negative effects of injuries and surgeries.…”
Section: Introductionmentioning
confidence: 99%